Empowering Coastal Communities Through Sustainable Mangrove Ecosystem Management - Mutiara Indah Safitri; Cahyo Wulandari (Jurnal Pengabdian, Riset, Kreativitas, Inovasi, dan Teknologi Tepat Guna, 2025)
The mangrove ecosystem in Berahan Kulon Village, Demak Regency, plays a vital role as a natural barrier against coastal abrasion and as a key support for the local coastal economy. Despite its significant natural resource potential, the area faces serious challenges due to environmental degradation, domestic waste pollution, and the lack of integrated and sustainable management. The main issues identified include limited community access to spatial zoning data and the absence of village-level regulations that ensure sustainable conservation and utilization. This study is part of the KKN-PPM (Community Service Learning and Empowerment Program) UGM Wedung Unit 2025, which aims to empower coastal communities by enhancing their capacity and active participation in sustainable mangrove ecosystem management. The activities were carried out through field observations, in-depth interviews, satellite image analysis, and participatory mentoring involving training sessions and the inclusive preparation of village-based management documents. The results indicate an increase in community understanding and awareness of the ecological functions of mangroves, along with greater involvement in conservation and rehabilitation activities. The program outcomes include the implementation of double-row planting techniques in critical zones, the establishment of a village-level mangrove management group, the formulation of a Village Regulation on mangrove protection, and the installation of educational information media in coastal areas. Furthermore, the mangrove area has begun to develop as an educational ecotourism space integrating coastal, pond, and mangrove forest areas to support a conservation-based local economy. This community engagement initiative contributes to strengthening social and institutional capacities, enhancing coastal resilience to abrasion, and creating a sustainable, empowerment-based mangrove management model aligned with Sustainable Development Goals (SDGs) 13 (Climate Action), 14 (Life Below Water), and 15 (Life on Land).